2011
DOI: 10.1002/cta.623
|View full text |Cite
|
Sign up to set email alerts
|

On IIR‐based bit‐stream multipliers

Abstract: SUMMARYWe analyze the existing bi-level IIR-based bit-stream multiplier and propose selection criteria for the key design parameter governing droop and phase linearity. Based on the proposed choice of parameter, we then extend the bi-level design to tri-and quad-level architectures that offer better signal-to-noise performance. Hardware complexity and noise performance of these designs are also contrasted with previously proposed FIR-based bit-stream multipliers. Useful design guidelines are subsequently drawn. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The work that was commenced by the authors in [22] and progressed by the ones in [8,24] has been reported by many, such as in [1-4, 7, 25-28]. More recently sigma-delta modulation based bit-stream adder and multiplier modules have been described in [29,30].…”
Section: Sigma-delta Modulation Based Fast Filtersmentioning
confidence: 99%
See 4 more Smart Citations
“…The work that was commenced by the authors in [22] and progressed by the ones in [8,24] has been reported by many, such as in [1-4, 7, 25-28]. More recently sigma-delta modulation based bit-stream adder and multiplier modules have been described in [29,30].…”
Section: Sigma-delta Modulation Based Fast Filtersmentioning
confidence: 99%
“…Bit-stream arithmetic modules with bi-, tri-, and quad levels are described in [30,32,47,48]. In these cases, hardware implementation of the arithmetic modules is done in Xilinx Virtex-5 using two's complement representation.…”
Section: Vlsi Analysis Of σδM Based Bit-stream Circuitsmentioning
confidence: 99%
See 3 more Smart Citations